ANALISIS PEMANFAATAN SMARTPHONE SEBAGAI MEDIA BELAJAR DARING PADA SISWA SEKOLAH DASAR SDN 5/33 MATTOANGIN PANGKEP - Ahmad Dachlan (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2022)
The purpose of this study is to describe the use of smartphones as an online learning medium for students at SDN 5/33 Mattoangin Pangkep. This research is a type of qualitative research with a phenomenological approach, where this study examines the use of smartphones as an online learning medium for elementary school students. The subjects in this study were teachers and students. Data collection techniques in this study included interview, observation, and documentation techniques. In analyzing qualitative data, it was divided into three stages of activity, namely data reduction, data presentation, and drawing conclusions. The results of smartphone research can be used by students of Mattoangin Pangkep 5/33 Elementary School as a medium of communication between students or teachers, as a medium for searching for information related to learning materials (learning resources), as a medium for easily conducting online meetings, as a medium for storing learning materials, and as a medium to facilitate the task of teachers and students. The smartphone application that is used as an online learning medium during the pandemic is WhatsApp, because this application is very familiar to use in everyday life Keywords: Smartphones, Teachers, Students, Online Learning